Colours of love in Polish and German (linguistics-cultural aspects) - Bawej, Izabela (Acta Universitatis Lodziensis. Folia Germanica, 2018)
The article describes six basic colour terms and their connotations concerning love on the basis of love between a woman and a man by prism of Poles and Germans.The analysis covers selected expressions with a colour element connoted a feeling of liking someone combined with sexual attraction to answer following questions: What colour does love have in Polish and German? What are physiological sources of the symbolism of love’s colours in Polish and German culture? Is the perception of love similar or different in both languages?